Verocytotoxin-producing Escherichia coli infection in family members of children with hemolytic uremic syndrome - Rivas, Marta (1996)
Fil: Rivas, Marta. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas; Argentina